Movimento clube da esquina: o canto de um povo, a voz de uma nação - Silveira, Cláudio Nazaré (2018)
Clube da Esquina constituted a cultural and musical movement that expressed, through songs, the Brazilian cultural values and the sociocultural context of an era in the regime of censorship. The research aims to analyze the dialogical relations in the lyrics of the songs: San Vicente; Nada será como antes; Milagre dos peixes; Fé cega, faca amolada; O que será and Credo, which constitute the corpus of work. For the theoretical support, the reflections of Bakhtin and of scholars of his work are taken up, such as: dialogical relations, statement, ideology and discursive genre. Dialogism is an interactive phenomenon of the language dimension and is always related to other discourses such as social, cultural, religious and political. The repertoire of analysis is based on the qualitative bibliographic review and the theoretical application to the analyzes. Through the analysis of the selected songs, it was verified the repression that Brazil and some Latin American countries were suffering at that moment, which is expressed through the lyrics of the compositions as a synthesis of the feeling of the people before the military dictatorship in the 1970s.